Pan-cancer analysis reveals DDX21 as a potential biomarker for the prognosis of multiple tumor types - Hu, Ankang; Wang, Yonghui; Tian, Jiahao; Chen, Zihan; Chen, Renjin; Han, Xufeng; Chen, Yang; Liu, Tingjun; Chen, Quangang (Frontiers in Oncology, 2022)
Background: DExD-box helicase 21 (DDX21) is an essential member of the RNA helicase family. According to the most recent research, DDX21 is involved in the carcinogenesis of various malignancies but only colorectal cancer. There has been no comprehensive research on the involvement of DDX21 in different types of cancer. Method: This study used the TCGA, CPTAC, GTEx, GEO, FANTOM5, BioGRID, TIMER2, GEPIA2, cBioportal, STRING, Metascape database and ‘Survival ROC’ software tool to evaluate the DDX21 gene expression, protein expression, immunohistochemistry, gene mutation, immune infiltration and protein phosphorylation in 33 TCGA tumor types, as well as the prognostic relationship between DDX21 and different tumors by survival analysis and similar gene enrichment analysis. Furthermore, cell counting kit-8 (CCK-8) and Transwell studies were used to assess the effect of DDX21 expression on LUAD cell proliferation and migration. Result: Overall, the DDX21 gene was highly expressed in most cancers. Overexpression of DDX21 was found to be associated with poor overall survival (OS) and disease-free survival (DFS) in survival analysis. Notably, we found that DDX21 mutations were most common in uterine corpus endometrial carcinoma (UCEC) (> 5%). Additionally, we found that the expression of DDX21 positively correlated with the degree of infiltration of CAF and CD8+ cells in several tumor types. And the study found a large number of genes co-expressed with DDX21. Through gene enrichment analysis, it was found that DDX21 was closely related to RNA metabolism or ribosomal protein production. Ultimately, in vitro investigations with the LUAD cell revealed that DDX21 expression was positively correlated with cell proliferation and migration capacity, which was consistent with the prior bioinformatics study. Conclusions: The above results indicate that DDX21 is commonly overexpressed in a variety of cancers, and overexpression in some cancers is associated with poor prognosis. Immune infiltration and DDX21-related gene enrichment analysis indicated that DDX21 may affect cancer development through mechanisms that regulate tumor immunity, RNA metabolism or ribosomal protein synthesis. This pan-cancer study revealed the prognostic value and oncogenic role of DDX21.